Pengaruh Penggunaan Media Sosial Dan Religiositas Islam Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Pada Karyawan Amdk Di Indonesia - Della Rista Pratiwi; Ahmad Ajib Ridlwan; A’rasy Fahrullah; Yan Putra Timur (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of social media usage and Islamic religiosity on employee performance, with job satisfaction as a mediating variable, among bottled drinking water (AMDK) industry employees in Indonesia. A quantitative approach was used with a non-probability purposive sampling technique, involving 214 respondents. Data were collected through online questionnaires, then analyzed using SPSS 24 for descriptive analysis and Smart PLS 4 for structural model analysis. The results show that social media usage and Islamic religiosity, both directly and indirectly (through job satisfaction), positively and significantly affect employee performance. This study enriches the understanding of the relationship between these variables in the context of the AMDK industry in Indonesia, while highlighting the importance of optimizing social media usage and integrating religious values to enhance employee performance.